(untitled) (International Journal of Nursing Education, 2019)
This qualitative research study using a heuristic, descriptive phenomenological approach explored the lived experience of 12 DNPs who have returned to in pursuit of a PhD in nursing. Three themes were identified from the study participates: Wanting to Know Something More, Social-Individual Tensions, and Challenges to Transformational Learning. Based on the study findings, the DNPs desire to expand on their limited research knowledge and the tensions and challenges to transformational learning surrounding this quest were worth it as the participants gained personal and professional fulfillment.